2015
DOI: 10.1155/2015/839253
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Relationship with Metabolic Syndrome in Class III Obesity Individuals

Abstract: Introduction. Obesity is represented mainly by abdominal obesity and insulin resistance (IR), both present in most individuals diagnosed with metabolic syndrome (MS). IR is the key risk factor in the pathogenesis of nonalcoholic fatty liver disease (NAFLD). Objective. To relate NAFLD to MS in class III obese individuals. Methodology. A descriptive cross-sectional study with class III obese individuals, aged ≥ 20–60 years. Blood pressure measurement, weight, height, body mass index (BMI), waist circumference (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
6
0
4
Order By: Relevance
“…Importantly, XOD, an enzyme involved in the production of UA from purine nucleotides, is an important source of oxidative stress. Numerous recent studies have indicated that metabolic syndrome (MS), including NAFLD or steatohepatitis (NASH), is likely related to hyperuricemia 22 . Xu C et al .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, XOD, an enzyme involved in the production of UA from purine nucleotides, is an important source of oxidative stress. Numerous recent studies have indicated that metabolic syndrome (MS), including NAFLD or steatohepatitis (NASH), is likely related to hyperuricemia 22 . Xu C et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of metabolic syndrome, diabetes mellitus, and hypertension was attenuated in multivariate analysis, perhaps due to the overwhelming influence of the strong association between the risk of NASH and the three constituent variables of the CLA score. Indeed, in other studies that did not consider the influence of hepatic fibrosis and steatosis, metabolic syndrome, diabetes mellitus, and hypertension were selected as independent predictors of NASH [ 41 , 42 ]. Further studies with larger sample size might be required to investigate whether the addition of metabolic syndrome, diabetes mellitus, and hypertension can enhance the overall prediction accuracy of the CLA score.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is more common in clinical practice and can seriously impact the quality of a patient’s life. The current clinical treatments for NAFLD include insulin sensitization agents, lipids, diet pills, antihypertensive agents, cell protective agents, anti-inflammatory cytokine antioxidants and other types (McCullough, 2004, Cordeiro et al, 2015). In recent years, with improvements of the living standards and the changes of the diet structure of the people, the incidence of NAFLD has increased year by year, but the pathogenesis is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%